2006
DOI: 10.1645/ge-544r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Prevalence and Abundance of Metacercariae in the Pulmonate Snail Lymnaea Stagnalis in Chany Lake, West Siberia, Russia: Long-Term Patterns and Environmental Covariates

Abstract: Infrapopulations of trematode metacercariae were monitored in the snail Lymnaea stagnalis over 17 yr (1982-1999) at Chany Lake, Novosibirskaya Oblast', Russia. Eighteen trematode species were recorded. Patterns of occurrence varied from 4 species (Echinoparyphium aconiatum, Echinoparyphium recurvatum, Moliniella anceps, and Cotylurus cornutus) that persisted at relatively high prevalence (> 60% of samples) across sites, seasons, and years, to species that were very rare and sporadic in occurrence. The stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The planorbid snails, including Physa alexandrina, Physa fontinalis, Planorbis planorbis, Lymnaea pervia, Lymnaea peregra, Valvata piscinalis, and Radix auricularia coreana shed the cercariae [78][79][80], and the metacercariae encyst in tadpoles and frogs of Rana temporaria and also in snails, P. planorbis, Lymnaea sp. [6], R. auricularia coreana [80], and Lymnaea stagnalis [81]. House rats [75], wild rats (Arvicanthis niloticus) [82], and species of birds are natural definitive hosts [48].…”
Section: Echinochasmus Liliputanus (Looss 1896) Odhner 1910mentioning
confidence: 99%
“…The planorbid snails, including Physa alexandrina, Physa fontinalis, Planorbis planorbis, Lymnaea pervia, Lymnaea peregra, Valvata piscinalis, and Radix auricularia coreana shed the cercariae [78][79][80], and the metacercariae encyst in tadpoles and frogs of Rana temporaria and also in snails, P. planorbis, Lymnaea sp. [6], R. auricularia coreana [80], and Lymnaea stagnalis [81]. House rats [75], wild rats (Arvicanthis niloticus) [82], and species of birds are natural definitive hosts [48].…”
Section: Echinochasmus Liliputanus (Looss 1896) Odhner 1910mentioning
confidence: 99%
“…The most prevalent metacercariae were those of E. aconiatum and E. recurvatum (both family Echinostomatidae) and C. bithyniae (Cyathocotylidae). In previous studies Yurlova et al (2006), and Serbina, (2014) showed that, metacercariae of E. aconiatum, were recorded in more than 70 % of samples of Lymnaea stagnalis and samples of B. troscheli in Chany Lake (South-West Siberia, Russia).…”
Section: Discussionmentioning
confidence: 94%
“…Snail density was looked for to be in a natural range (Yurlova et al, 2006). For acclimation to the experimental conditions, the individuals of L. stagnalis were precultured for 5 d in the laboratory (in 10 L of soft water, 20°C) before starting the experiment.…”
Section: Methodsmentioning
confidence: 99%